Mistaken conclusions about systemic exercise intolerance disease being comparable to research case definitions of CFS: A rebuttal to Chu et al. Issue 4 (2nd October 2017) - Jason, Leonard A.; Sunnquist, Madison; Gleason, Kristen; Fox, Pamela
ABSTRACT: The recent article by Chu et al. contrasted different case definitions that have been used to describe chronic fatigue syndrome (CFS) and myalgic encephalomyelitis (ME). In particular, their study compared the new Institute of Medicine (IOM) criteria for systemic exertion intolerance disease (SEID) with three other ME and CFS case definitions. We appreciate these investigators attempting to use and operationalize the new IOM criteria; however, we disagree with their main conclusion that the percentage of patients selected by the IOM criteria is comparable to the percentage selected by other research case definitions. This conclusion could potentially encourage investigators to use the IOM criteria for research purposes. In this commentary, we discuss our observations of the Chu et al. article with respect to their methodology, illustrating how the conclusions of an investigation can be influenced by the manner in which case definitions are operationalized.